1992
DOI: 10.1021/la00046a030
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte adsorption: a subtle balance of forces

Abstract: The adsorption of polyelectrolytes on oppositely charged surfaces is investigated by numerical calculations based on a recent model for polyelectrolyte adsorption by Bóhmer et al.,1 which is an extension of the self-consistent-field theory of Scheutjens and Fleer for adsorption of uncharged homopolymers. First, the effects of salt concentration, segment charge, and surface charge density are described for the case of pure electrosorption. It appears that the adsorption always decreases with increasing salt con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
335
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(377 citation statements)
references
References 0 publications
40
335
1
1
Order By: Relevance
“…The practical relevance of polyion adsorption has generated substantial theoretical [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and experimental 6,16,[20][21][22][23][24][25][26][27][28][29][30][31][32] efforts. As mentioned above, surface interactions in polyelectrolyte solutions can often be regulated by increasing or decreasing the addition of simple salt.…”
Section: Introductionmentioning
confidence: 99%
“…The practical relevance of polyion adsorption has generated substantial theoretical [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and experimental 6,16,[20][21][22][23][24][25][26][27][28][29][30][31][32] efforts. As mentioned above, surface interactions in polyelectrolyte solutions can often be regulated by increasing or decreasing the addition of simple salt.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions the classical one-gradient SCF theory predicts a slight undercompensation of the surface charge by adsorbed polyelectrolyte. 5 We found that in the framework of a two-gradient SCF model the equilibrium adsorbed amount near the plateau of the adsorption isotherm corresponds to noticeable overcompensation of the surface charge. To compare our results with predictions from Ref.…”
Section: Discussionmentioning
confidence: 79%
“…At high ionic strength, when the entropy gain of the small ions is less important, it is possible to displace the polymer from the interface. [1][2][3][4][5][6] At very low ionic strength the adsorption tends to saturate to a value for the adsorption that is very close to the exact surface charge compensation. Indeed, the exact surface charge compensation is expected at very low ionic strength.…”
Section: Introductionmentioning
confidence: 92%
“…Adsorption experiments and modeling have been used to gain information about formed layers of polyelectrolytes (Van de Steeg et al 1992;Fleer et al 1993). Adsorption studies using QCM-D and SPR techniques have revealed that polyelectrolytes adsorb differently depending on their chemical properties, such as molar mass and charge density, onto model cellulose or silica surfaces (Tammelin et al 2004;Kontturi et al 2008;Strand et al 2017).…”
Section: Introductionmentioning
confidence: 99%